Analisis Deskripsi Tentang Dua Macam Gembala (Zakharia 11:4-17) Dan Implikasinya Terhadap Gembala Jemaat - Marni Ruru'; Detris Putri Salluk; Sintike Lois; Sri Wahyuni Pakiding (Jurnal Teologi Praktika, 2022)
This study aims to examine the meaning and meaning of two shepherds implied in the book of Zechariah 11: 4-17. Shepherd is a person who will be made as a guide for the sheep, He is a person who is specially called by God to care for the sheep. A pastor is characterized by a responsibility that must be carried out with sincerity, gratitude and a willingness to perform the service. The reality that happens over time is that many shepherds neglect their duties and responsibilities so that some of the attitude of a shepherd that is not appropriate. This has triggered the existence of several kinds of shepherds within the Church today. The emergence of various pastors in the Church certainly greatly influenced the growth and development of the congregation. Therefore, to explain and find out more about it, the research method used is descriptive analysis. The approach that the writer uses in this research is reference books and literature research. After describing it descriptively, the findings in this study are (1) Two types of shepherds (2) Doing shepherding properly (5) there is rejection of the shepherd (4) Being a true Shepherd. With the aim that a pastor can realize his responsibility and through that awareness, the church can grow on the right path.Keywords: Kinds of Shepherd, Shepherding, Sheep, Responsibility